An active inductor employing a new four terminal floating nullor transconductance amplifier (FTFNTA). Issue 5 (3rd May 2020) - Tarunkumar, Huirem; Shantikumar Singh, Yumnam; Ranjan, Ashish
ABSTRACT: In this scientific study, a new analog active building block named as four terminal floating nullor transconductance amplifier (FTFNTA) is implemented. The FTFNTA design offers a combined essence of both traditional four terminal floating nullor (FTFN) and an operational transconductance amplifier (OTA). The FTFNTA design is extended for the design of a lossless floating and grounded inductor simulator with few passive components. In addition, the performance and usefulness of the proposed inductor topology are also expanded for active filter applications: higher-order Butterworth high-pass filter and current mode multifunction filter. The functionality of the CMOS-based FTFNTA is integrated with a 0.18 µm Taiwan Semiconductor Manufacturing Company (TSMC) CMOS technology. Moreover, the FTFNTA is also realised using the current feedback operational amplifier (CFOA/AD844) and OTA (OTA/CA3080) of a commercially available IC to test the viability of the proposed inductor design. Finally, an application based on the inductor topology and its impedance characteristics are well analysed via PSPICE simulation.